Our Cyberbodies, Ourselves: Conceptual Grounds for Teaching Commodities to Write. - Harrison, Stanley D. (JAC: A Journal of Composition Theory)
Focuses on the conceptual grounds for teaching student writers in computer classrooms. Consideration of the problem of computer writing; Assessment of the conjuncture of consumer culture and cyberspace; Education of student cyber writers to intervene in subject formation at the level of computer software.